Biology, Ecology, and Management of Nonnative Ambrosia Beetles (Coleoptera: Curculionidae: Scolytinae) in Ornamental Plant Nurseries. (29th April 2016) - Ranger, Christopher M.; Reding, Michael E.; Schultz, Peter B.; Oliver, Jason B.; Frank, Steve D.; Addesso, Karla M.; Hong Chong, Juang; Sampson, Blair; Werle, Christopher; Gill, Stanton; Krause, Charles
Abstract: Xylosandrus germanus (Blandford) and Xylosandrus crassiusculus (Motschulsky) (Coleoptera: Curculionidae: Scolytinae) are two of the most damaging nonnative ambrosia beetle pests in ornamental plant nurseries. Adult females tunnel into the stems and branches of host plants to create galleries with brood chambers. Hosts are infected with symbiotic Ambrosiella spp. fungi that serve as food for the larvae and adults. Plants can also become infected with secondary opportunistic pathogens, including Fusarium spp. Both X. germanus and X. crassiusculus have broad host ranges, and infestations can result in "toothpicks" of extruded chewed wood and sap flow associated with gallery entrances, canopy dieback, stem and trunk cankers, and plant death. Beetles efficiently locate and preferentially attack living, weakened plants, especially those physiologically stressed by flooding, inadequate drainage, frost injury, or winter injury and low temperature. Maintaining plant health is the foundation of a management plan. Vulnerable hosts can be partially protected with preventive pyrethroid applications in the spring before peak flight and attack, which are monitored using ethanol-based trapping tactics.